TECHNOLOGY-DRIVEN INNOVATION STRATEGIES TO ENHANCE ENTREPRENEURIAL COMPETITIVENESS IN A DYNAMIC GLOBAL MARKET ECOSYSTEM - Said Ahmad, Muh. Ihsan (PT. LITERASI SAINS NUSANTARA, 2024)
This study aims to analyze technology-driven innovation strategies to enhance entrepreneurial competitiveness in a dynamic global market ecosystem. The research employs a qualitative literature review and descriptive analysis, drawing from 20 selected articles sourced from Google Scholar between 2004–2024. The findings highlight that disruptive technologies such as artificial intelligence, blockchain, big data analytics, and the Internet of Things have played a pivotal role in creating new value and operational efficiencies. Case studies of Tokopedia, Ruangguru, and Traveloka illustrate how disruptive technologies help entrepreneurs improve service personalization, expand markets, and adapt to rapid changes in global markets. However, challenges such as low digital literacy, resource constraints, and the need for cross-sector collaboration remain significant. The study recommends collaborative strategies, enhanced digital literacy, and supportive policies to maximize the potential of disruptive technologies in fostering sustainable entrepreneurial competitiveness.